1996
DOI: 10.1021/es9502132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fulvic Acid on Fe(II) Oxidation by Hydrogen Peroxide

Abstract: Iron redox cycling can catalyze the oxidation of humic substances and increase the rate of oxygen consumption in surface waters rich in iron and organic carbon. This study examines the role of Fenton's reaction [oxidation of Fe(II) by hydrogen peroxide] in this catalytic cycle. A number of competing processes were observed in model systems containing dissolved Fe, hydrogen peroxide, and Suwannee River fulvic acid. First, the effective rate constant of Fenton's reaction increased with increasing fulvic acid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
250
4
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(265 citation statements)
references
References 49 publications
9
250
4
2
Order By: Relevance
“…Apesar do uso de cobre ou cobalto nesses sistemas apresentar grande eficiência, a toxicidade desses metais pode causar outros problemas ambientais. 47,48 , seqüestrando os radicais livres ou estimulando a produção destes para degradação de xenobióticos 10,15,[47][48][49] , ou ainda incorporando os produtos de oxidação de xenobióticos em suas estruturas poliméricas 10,15 . A Tabela 2 compila alguns trabalhos que avaliaram a participação de substâncias húmicas na degradação de xenobióticos por reações do tipo Fenton.…”
Section: •-unclassified
“…Apesar do uso de cobre ou cobalto nesses sistemas apresentar grande eficiência, a toxicidade desses metais pode causar outros problemas ambientais. 47,48 , seqüestrando os radicais livres ou estimulando a produção destes para degradação de xenobióticos 10,15,[47][48][49] , ou ainda incorporando os produtos de oxidação de xenobióticos em suas estruturas poliméricas 10,15 . A Tabela 2 compila alguns trabalhos que avaliaram a participação de substâncias húmicas na degradação de xenobióticos por reações do tipo Fenton.…”
Section: •-unclassified
“…The pH value was detected by pH meter (pHS-3E, Shanghai, China). The concentration of aqueous iron ions were determined by the ferrozine method [32].…”
Section: B Procedures and Approachmentioning
confidence: 99%
“…We disregard here complexation of Fe(II) by organic ligands. Ferrous iron complexes have been suggested to be possibly responsible for the long residence time of Fe(II) in the SOIREE iron fertilization experiment (Croot et al, 2001), but have only been demonstrated in riverine or coastal waters with high fulvic acid concentrations Sulzberger, 1996 andRose andWaite, 2003). However, such Fe(II) specific ligands may be difficult to identify using current techniques when they are at low abundance (e.g., Croot et al, 2007Croot et al, , 2008.…”
Section: Theoretical Frameworkmentioning
confidence: 99%